2020
DOI: 10.13080/z-a.2020.107.032
|View full text |Cite
|
Sign up to set email alerts
|

Increase in resistance to sulfonylurea herbicides in Alopecurus myosuroides populations in north-eastern Poland

Abstract: The number of herbicide-resistant populations of black-grass (Alopecurus myosuroides Huds.) in winter cereal crops in Europe is increasing, leading to serious restrictions in winter cereal production. The aim of this study was to evaluate the reaction of five A. myosuroides populations: four suspected as being herbicide-resistant and one susceptible to mesosulfuron + iodosulfuron-based herbicide (acetolactate synthase (ALS) inhibitor). Mutation events in domains A and B of the als gene, and the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The UK's latest report showed that the herbicide resistance-prone, outcrossing A. myosuroides exhibits low genetic differentiation amongst eld-collected populations, with some geographical (latitudinal and longitudinal) clines in genetic diversity and isolation by distance [23]. In Poland, herbicide-resistant blackgrass populations are mostly found in winter wheat, especially in the northeastern parts of the country [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The UK's latest report showed that the herbicide resistance-prone, outcrossing A. myosuroides exhibits low genetic differentiation amongst eld-collected populations, with some geographical (latitudinal and longitudinal) clines in genetic diversity and isolation by distance [23]. In Poland, herbicide-resistant blackgrass populations are mostly found in winter wheat, especially in the northeastern parts of the country [24,25,26].…”
Section: Introductionmentioning
confidence: 99%